Sosialisasi Pemanfaatan Daun Sirih Di Desa Sambiroto, Kec. Baron Sebagai Obah Dari Kemu: Sosialization Of The Utilization Of Betel Leaves In Sambiroto Village, Kec. Baron As Obah Dari Kemul - Nur Septiani Megasari; Fransiscus Xaverius Sri Sadewo (Jurnal Mandala Pengabdian Masyarakat, 2021)
This research was motivated by the large number of unemployed people in Sambiroto Village which was caused by the Covid-19 pandemic. In addition, because there has never been any socialization regarding the development of community skills in the use of betel leaf. This research was conducted to be able to find out how the socialization of community skills development in Sambiroto Village, Kec. Baron in the use of betel leaf. The aim is to analyze the socialization of community skills development in Sambiroto Village, Baron District in the use of betel leaf. As well as being able to restore the community's economy for the better, thus this activity cannot be separated from the support of the village and the community itself. In this research, the method used is qualitative with a phenomenological approach. The approach taken is descriptive, namely by presenting data and descriptive format, with the aim of describing, summarizing the results of the data that has been obtained. The theory that the researcher uses is social, put forward by Max Weber. The results of this study are that the researchers designed various activities to use betel leaf as herbal snacks and as herbal medicine for the community of Sambiroto Village, Kec. Baron during the Covid-19 pandemic.